2001
DOI: 10.1007/bf03032606
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of diabetes mellitus in the patients with transitional cell carcinoma of urinary bladder

Abstract: The progression of bladder cancer to invasive disease is highly dependent on its ability to penetrate basement membrane of urothelium. Studies on diabetic nephropathy have shown a reduction in proteoglycan content of the glomerular basement membrane. Based on the well-known fact that proteoglycans are one of the main components of basement membrane and extracellular matrix we assessed the relationship between diabetes mellitus, bladder cancer incidence and its behavior. These studies include 252 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…We identified eight case-control studies [12][13][14][15][16][17][18][19], three cohort studies [20][21][22] and seven cohort studies of hospitalised diabetic patients using external population comparisons [23][24][25][26][27][28][29]. One case-control study [12] was excluded because no measure of the RR was reported and the RR could not be calculated.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified eight case-control studies [12][13][14][15][16][17][18][19], three cohort studies [20][21][22] and seven cohort studies of hospitalised diabetic patients using external population comparisons [23][24][25][26][27][28][29]. One case-control study [12] was excluded because no measure of the RR was reported and the RR could not be calculated.…”
Section: Search Resultsmentioning
confidence: 99%
“…Studies in animals support a potential role of IGF-I in bladder tumorigenesis [42]. Diabetes is also associated with an increased risk of urinary tract infection [43], which has been related to bladder cancer risk [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the epidemiological relationship between these two important diseases has not been studied until now. Recently, there are noteworthy epidemiological studies concerning the association between diabetes and transitional cell carcinoma of the bladder (17)(18)(19)(20).…”
Section: Diabetes Screening Of Oral Cancer Patientsmentioning
confidence: 99%
“…Twenty three relevant studies were retrieved about incidence, including eight case-control studies (O'Mara et al, 1985;Risch et al, 1988;Vecchia et al, 1994;Kravchick et al, 2001;Ng et al, 2003;Rousseau et al, 2006;MacKenzie et al, 2011;Attner et al, 2012), fifteen cohort studies (Ragozzino et al, 1982;Adami et al, 1991;Wideroff et al, 1997;Tripathi et al, 2002;Zendehdel et al, 2003;Coughlin et al, 2004;Swerdlow et al, 2005;Jee et al, 2005;Inoue et al, 2006;Larssona et al, 2008;Li et al, 2011;Tseng et al, 2011;Zhang et al, 2012;Newton et al, 2012;Prizment., 2013), comprising a total of 643,683 patients with DM and 4,819,656 patients without DM. The characteristics of selected studies are summarized in Table 1.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The characteristics of selected studies are summarized in Table 1. In some studies, the integral number of male and female were not reported (O'Mara et al, 1985;Risch et al, 1988;Kravchick et al, 2001;Ng et al, 2003;Inoue et al, 2006;Rousseau et al, 2006;Attner et al, 2012;Prizment et al, 2013;Verlato et al, 2013), and two of them were only included with women (Tripathi et al, 2002;Prizment et al, 2013), also another two of them were only included with men (Larssona et al, 2008;Attner et al, 2012), so there were 279,508 male and 291,644 female patients with DM, 2,199,602 male and 1,742,232 female patients without DM, respectively. There were ten studies with North America region, eight for Europe region and five with Asia region, respectively.…”
Section: Description Of Studiesmentioning
confidence: 99%